Mapping the non-coding RNA landscape in ataxia telangiectasia: a scoping review of ATM dependent miRNA and lncRNA dysregulation - Muhammad Junaid Iqbal; Usman Ameen; Hamza Tanveer; Laraib Israr; Anastasia Ricci; Gianluca Morganti; Muhammad Jawad Khan; Michele Menotta (Molecular Biology Reports, 2025)
Ataxia-Telangiectasia (A-T) is caused by biallelic Ataxia-Telangiectasia Mutated (ATM) protein mutations and is hallmarked by neurodegeneration, immunodeficiency and cancer susceptibility. Emerging work suggests that non-coding RNAs are integral to the ATM driven DNA damage response, yet the scope of non-coding RNA perturbation in A-T has not systematically mapped. This study is done to chart and synthesize all primary evidence on ncRNA dysregulation in A-T and to identify mechanistic gaps and research priorities. The evidence base comprises a total of five studies focused exclusively on microRNAs and long non-coding RNAs. Baseline sequencing of 20 patients revealed consistent downregulation of miR-195-5p, miR-30a-5p and miR-342-3p. Low dose γ-irradiation of ATM-null lymphoblastoid cell lines produced an exaggerated bidirectional shift (8 microRNAs upregulated, 6 downregulated) versus wild-type, whereas primary T-cells showed largely ATM independent rises of miR-34a-5p and miR-182-5p. A lymphoblastoid cell lines study distinguished 22 recessive or dominant radiation-responsive microRNAs. Long non-coding RNAs profiling identified 149 transcripts that require functional ATM for induction and three uniquely upregulated in A-T cells. No circular RNA study in A-T is observed till date. The ncRNA research in A-T is nascent with five studies present a miRNA dysregulation and an ATM-dependent lncRNA surge that is lost in A-T, but leave circRNAs, neuronal tissues and functional validation unexplored. Intermediate dose stress models, total and small RNA-seq under DNA damage and oxidative stress, and CRISPR rescue/knockout screens in patient derived organoids are immediate priorities for exploring the role of ncRNAs as therapeutic targets in A-T.